2019
DOI: 10.1210/jc.2019-00240
|View full text |Cite
|
Sign up to set email alerts
|

In a Free-Living Setting, Obesity Is Associated With Greater Food Intake in Response to a Similar Premeal Glucose Nadir

Abstract: Purpose Changes in blood glucose levels have been shown to influence eating in healthy individuals; however, less is known about effects of glucose on food intake in individuals who are obese (OB). The goal of this study was to determine the predictive effect of circulating glucose levels on eating in free-living OB and normal weight (NW) individuals. Methods Interstitial glucose levels, measured with a continuous glucose mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Along with clinical applications, CGM systems are also widely used for research [6][7][8][9][10] to provide comprehensive glycaemic profiles, including glucose nadir [7], glucose peak [9] and area under the curve [10]. These devices are often utilised in studies under freeliving conditions, as they remove the barrier of collecting blood samples in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Along with clinical applications, CGM systems are also widely used for research [6][7][8][9][10] to provide comprehensive glycaemic profiles, including glucose nadir [7], glucose peak [9] and area under the curve [10]. These devices are often utilised in studies under freeliving conditions, as they remove the barrier of collecting blood samples in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies using CGM in people without diabetes have been scarce, and glucose variability in seemingly healthy people has not been fully studied. Recently, Kim et al examined the CGM of healthy nondiabetic individuals in a free-living setting and found that glucose nadirs before a meal predicted subsequent hunger and food intake [ 21 ]. In addition, using CGM in their prospective cohorts, Wyatt et al showed that the average postprandial glucose dips 2–3 h after a standardized meal (890 kcal, 86 g of carbohydrates, 53 g of fat, 16 g of protein, and 2 g of fiber, ingested within 10 min) relative to baseline level are significantly associated with an increase in hunger postprandial for 2–3 h, a shorter time until the next meal, and greater postprandial energy intake [ 22 ].…”
Section: Blood Glucose and Appetitementioning
confidence: 99%
“…A growing body of work has suggested that obesity is associated with changes in central sensing and utilization of glucose [5][6][7]. Functional magnetic resonance imaging (MRI) studies have shown that the regional blood-oxygen-level-dependent (BOLD) signal, which is often used as a surrogate measure for brain activity, is different in individuals with obesity, particularly when peripheral blood glucose levels are controlled using hyperglycemic and hypoglycemic clamp studies [6,7].…”
Section: Introductionmentioning
confidence: 99%